Dimethyladenosine Transferase 1 Homolog Promotes Human Gastric Carcinoma Cell Proliferation and Inhibits Apoptosis via the AKT Pathway - Liu, Guang-yi; Wang, Huan; Ran, Rui; Wang, Yi-cheng; Li, Yang (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Our previous work identified the dimethyladenosine transferase 1 homolog as a novel prognostic factor for detecting human gastric carcinoma with high sensitivity and specificity. The high expression of dimethyladenosine transferase 1 is closely associated with the occurrence and progression of gastric carcinoma. However, the underlying mechanism of dimethyladenosine transferase 1 for the occurrence and development of gastric carcinoma is not well elucidated yet. Materials and Methods: In our present study, the biological role of dimethyladenosine transferase 1 on cell proliferation, apoptosis, and cell cycle progression in human gastric carcinoma cells was investigated through in vitro and in vivo assays by the overexpression and knockdown of dimethyladenosine transferase 1 2-way authentication method. Results: We found that the overexpression of dimethyladenosine transferase 1 significantly promotes cell proliferation (P < .001) and inhibition of cell apoptosis (P < .01) in SGC-7901 cells. However, the in vivo experiment results of the knockdown dimethyladenosine transferase 1 using small interfering RNAs in the MKN-45 are just the opposite. Reverse-transcriptase polymerase chain reaction and western blotting analysis revealed that overexpressed dimethyladenosine transferase 1 in SGC-7901 cells significantly activated the AKT pathway compared to control cells. In contrast, we found that apoptosis genes such as Caspase-3 and Caspase-9 were downregulated in those cells. The xenograft nude mice model exhibited increased tumor growth (P < .01) and weight loss (P < .01), with the overexpression of dimethyladenosine transferase 1 homolog in the SGC-7901 cells. These results have been further confirmed through backward verification in dimethyladenosine transferase 1 knockdown cells. Conclusions: Taken together, our results indicated that the dimethyladenosine transferase 1 plays a crucial role in stimulating cancer cell proliferation and contributes to apoptosis resistance in human gastric carcinoma. Meanwhile, it provides a potential therapeutic target for gastric carcinoma treatment and is worthy of further studies. Cite this article as: Liu G, Wang H, Ran R, Wang Y, Li Y. Dimethyladenosine transferase 1 homolog promotes human gastric carcinoma cell proliferation and inhibits apoptosis via the AKT pathway. Turk J Gastroenterol. 2023;34(8):802-812.